Relative efficacy of different types of exercises in the treatment of knee and hip osteoarthritis: A network meta-analysis of randomised controlled trials - Goh, Siew Li (2019)
Background: The need for exercise in osteoarthritis (OA) has been long-recognised, leading international guidelines and experts to universally endorse exercise as a core treatment for OA. However, currently there is no consensus on which type of exercise is most beneficial, and there is clear differentiation of exercise effects across different OA outcomes.